ANALISIS PERUBAHAN LUAS RUANG TERBUKA HIJAU DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA DI JAKARTA SELATAN - Santun RP Sitorus; Widya Aurelia; Dyah R Panuju (http://arl.faperta.ipb.ac.id/, 2011)
South Jakarta is one of region in the DKI Jakarta facing an enormous growth in all aspects of development. The increasing of development activities and regional cause increase land uses dynamic. Fixed land supply compare with the increasing demand causing land use change particularly greenery open space in South Jakarta. This research aims are: (1) to identify changing of greenery open space of South Jakarta, and (2) to find out population, infrastructure, anddevelopment growth rate of South Jakarta; and (3) to identify factors influencing change of greenery open space and relationship among the factors. The result shows that greenery open space in the period of 2002-2007 decreased about 362,21 hectare from 1299,22 hectares in 2002 to 937,01 hectares in 2007. In the same period number of population and population density increased 0,7% per year while immigrants declined -23% per year. The region of South Jakarta in 2003 showed hierarchy III village was dominant (43 villages), while number of hierarchy II and I village, were 17villages and 5 villages, respectively. In 2006 number of villages categorized on hierarchy II showed increasing to be 19 villages while hierarchy III decreasing tobe 41 villages and hierarchy I was constant in number. Regional development could be due to growth on infrastructure development such as educational facility, health facility, and commercial area. The number of educational, health, and commercial facilities grew during the period of 2003-2006 with rate of 4,8%, 7,1%, and 20% per year, respectively. Regression analysis was utilized to identify factors influencing greenery open space area change. According to the result, land allocated for greenery open space in Jakarta’s spatial plan (RTRW) being the major factor affecting the change. The other factors were growth of health facilities, immigrants, population density, and educational facilities.